Adaptação transcultural para o português brasileiro e análise das propriedades de medida da Spinal Cord Injury Falls Concern Scale (SCI-FCS) - Gabriela Afonso Galante Maia (2020)
Introduction: Falls after a spinal cord injury (SCI) are frequent in wheelchair users. In addition to physical injuries, it may result in excessive concern about falling and impact on quality of life and restrictions on daily and social activities. The Spinal Cord Injury Falls Concern Scale (SCI-FCS), developed in English language, aims to assess the concern about falling in this population. Objectives: to translate and cross-culturally adapt the SCI-FCS to Brazilian Portuguese, to evaluate its measurement properties and to investigate the association between clinical variables and SCI-FCS-Brazil scores. Methods: methodological research design. The SCI-FCS was translated and culturally adapted to Brazilian Portuguese according to guidelines. The measurement properties were verified through the Rasch Analysis; internal consistency, using Cronbach's α coefficients; total score test–retest reliability and level score test–retest reliability, using ICC and quadratic weighted kappa coefficient, respectively. Spearman's correlation (α = 0.05) coefficients were calculated to verify the associations between age, time since spinal cord injury, neurological level, occurrence of fall on the past year, fear of falling and the scores of the SCI-FCS-Brazil. Results: one hundred thirty individuals were enrolled in the study. Mean time since SCI occurrence was 4 (5) years, 62% thoracic level, 54% reported at least one fall in the previous year. The median SCI-FCS-Brazil score was 27 (22-34). Cronbach’s α was 0.95; ICC was 0.92 (IC95%:0.86-0.95) for the total score test-retest reliability and Kappa ranged from 0.04 to 0.87 (IC95%: 0.01-1) for the item level reliability. Rasch analysis reliability index was 0.81 and 0.98 and separation index was 2.10 and 6.25 for persons and items, respectively. The mean Infit MnSq values for items were 1.08 and for persons, 0.99. SCI-FCS-Brazil scores showed a poor and negative association with time since spinal cord injury (p=.019) and occurrence of fall on the past year (p=.028) and a moderate and positive association with fear of falling (p=.001). Conclusions: SCI-FCS-Brazil showed adequate measurement properties and association with clinical variables. It is important to ensure a correct SCI-FCS scores interpretation during its application. Its use in Brazilian wheelchair users with SCI is recommended to help defining rehabilitation strategies, mainly for individuals with greater concerns about falling and less time of SCI.